Cerebellopontine angle mass mimicking lingual nerve injury after dental implant placement: a case report. (September 2015) - Momota, Y; Kani, K; Takano, H; Azuma, M
Abstract This is a rare case report of a cerebellopontine angle (CPA) mass mimicking lingual nerve injury after a dental implant placement. Lingual nerve injury is a common complication following dental implant placement. CPA masses are likely to cause symptomatic trigeminal neuralgia, and thus can mimic and be easily confused with oral diseases. We experienced a case of CPA mass mimicking lingual nerve injury after dental implant placement. The patient was a 57‐year‐old Japanese female who complained of glossalgia. She underwent dental implant placement in the mandible before visiting our clinic. Panoramic x‐ray radiography revealed no abnormalities; the salivary flow rate by gum test was 7.0 ml/10 min. She was diagnosed with lingual nerve injury and secondary burning mouth syndrome. Vitamin B12 and oral moisturizer did not provide relief; furthermore, numbness in the lower lip emerged. A Semmes Weinstein test demonstrated elevation of her sensitivity threshold. Finally, magnetic resonance imaging revealed a 20‐mm diameter mass in the CPA. The patient is now being followed under conservative management. Our experience underscores the importance of including CPA mass in the differential diagnosis of dental diseases.